PEMETAAN BIBLIOMETRIK DAN ANALISIS TREN PENELITIAN MEDIA PEMBELAJARAN IPA DI SEKOLAH DASAR: IMPLIKASI PENGEMBANGAN MEDIA KARTU HEWAN BERBASIS BARCODE MELALUI PERMAINAN EDUKATIF - Fadhilah, Fadhilah; Tri Joko Raharjo; Sri Sumartiningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to map research trends in science learning media in primary schools using a bibliometric approach. Data were collected from Google Scholar and Crossref using Publish or Perish and analyzed with VOSviewer. The result reveal two main clusters: learning implementation and media development. Research trends shift toward technology based and game based learning. The findings indicate that barcode based animal card media has strong potential to enhance students’ engagement and conceptual understanding.